Endocrine Profile of an Ovariectomized Cynomolgus Monkey (Macaca fascicularis) with a Supernumerary Ovary - Ethun, Kelly F (American Association for Laboratory Animal Science, 2011)
For 21 mo after a bilateral ovariectomy, a 19-y-old ovariectomized cynomolgus macaque (Macaca fascicularis) continued to have menstrual cycles and measurable premenopausal estradiol and progesterone concentrations. Among these 10 menstrual cycles, 5 cycles were normal in duration and 5 were prolonged. At necropsy, a firm nodule was identified in the omental fat, and histologic evaluation confirmed the presence of ovarian tissue containing various stages of atretic follicles, a regressing corpora lutea, and a degenerating antral follicle. The endometrium and vaginal epithelium were atrophic. The occurrence of ectopic ovarian tissue in any form and location is a rare gynecologic condition in both women and nonhuman primates. Previously reported cases in nonhuman primates have been incidental findings at necropsy; therefore, the steroidogenic capacity and endocrine-related sequelae of such ovarian tissue in any nonhuman primate species is unknown. Based on structure, location, and relationship to normally situated ovaries, the ovarian tissue in this case was classified as a supernumerary ovary. To our knowledge, this is the first case report of a supernumerary ovary in a cynomolgus macaque. This report demonstrates that supernumerary ovaries in nonhuman primates can be biologically active for many years beyond sexual maturity and should be considered as a possible cause for vaginal bleeding and elevated ovarian hormone concentrations after ovariectomy.